A Descriptive Study On Teaching Speaking To The Tenth Grade Student Of Automotive Class At SMK Muhammadiyah 1 Blora In 2013/2014 Academic Year - Rosidayani, Dyah Ayun, Drs. Djoko Srijono, M.Hum, Aryati Prasetyarini, S.Pd, M.Pd (2014)
This research aims at describing the process of teaching speaking to the tenth grade student of automotive class at SMK Muhammadiyah 1 Blora in 2013/2014 academic year. Specifically, this research is aimed at describing the process of teaching speaking which will be explained in five different aspects: the goal, the techniques, the material, the media, and the evaluation, and describing the strength and weakness of the techniques applied in teaching speaking to the tenth grade students of automotive class in SMK Muhammadiyah 1 Blora. This reserach uses descriptive qualitative research. The subject of this research are the English teacher and the students in speaking class. The object of this researh is the teaching speaking activity. The method of collecting the data is by doing observation, interview, and documentation. The data of this research are the events of teaching speaking to the tenth grade students of automotive class. The results of this research show that: a) the goal of teaching speaking is to develop and to increase the students skill to speak to the others in a good language with confidence, b) the techniques used by the teacher are role playing, games, problem-solving, and discussion which are divided into 75% for presentation and 25% for explanation in each meeting, c) the materials for teaching speaking used by the teacher to the tenth grade students of automotive class are daily conversations and some dialogues about a job taken from the book "Look Ahead for the Senior High School" as the main material and some parts of daily newspaper, d) the media for teaching speaking is visual media, e) the evaluation for teaching speaking is that the teacher used oral speaking test as the students assessment instrument, f) the strength and the weakness of the techniques applied in teaching speaking are various but they are balanced, they are caused by the different skills and ability of the students and the condition of the class itself